DIFFICULTIES IN THE PROCESS OF INTERPRETATION AND STRATEGIES OF THEIR OVERCOMING - Герасименко, Ольга; Гончаренко, Анастасія (Modern engineering and innovative technologies, 2023)
The presented article outlines an extremely important problem in philological science, namely the difficulties faced by translators in the process of oral translation. Analysis of recent research and publications emphasizes the importance of cultural cha